Design and tensile properties of a bcc Ti-rich high-entropy alloy with transformation-induced plasticity. Issue 2 (4th March 2017) - Lilensten, Lola; Couzinié, Jean-Philippe; Bourgon, Julie; Perrière, Loïc; Dirras, Guy; Prima, Frédéric; Guillot, Ivan
ABSTRACT: A new bcc Ti-rich high-entropy alloy (HEA) of composition Ti35 Zr27.5 Hf27.5 Nb5 Ta5 was designed using the 'd-electron alloy design' approach. The tensile behavior displays a marked transformation-induced plasticity effect resulting in a high normalized work-hardening rate of 0.103 without loss of ductility when compared to the reference composition Ti20 Zr20 Hf20 Nb20 Ta20 . In this paper, a detailed microstructural analysis was performed to understand the deformation process, revealing architectural-type microstructures and a high volume fraction (65%) of internally twinned stress-induced martensite α ″ after mechanical testing. This study opens the way to mechanical properties optimization and enhancement of titanium-based HEAs by combining multiple alloying designs. IMPACT STATEMENT For the first time, proof is given that transformation-induced plasticity was triggered in a bcc refractory high-entropy alloy, leading to a twofold increase in the normalized work-hardening rate. GRAPHICAL ABSTRACT: